Pengetahuan Berhubungan dengan Kejadian Anemia pada Remaja - Dewi Ambarwati; Luluk Khusnul Dwihestie; Triani Yuliastanti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Due to its effect on the caliber of generations to come, iron deficiency anemia in teenage females is one of Indonesia's most pressing reproductive health concerns. Adolescents' awareness to autonomously adopt preventative actions is shaped mostly by their knowledge. The purpose of this research is to determine whether there is a correlation between the prevalence of anemia among teenage females in Boyolali Regency and their degree of education. Using a cross-sectional design, this study employs quantitative correlational analytic methods. An accidental sampling approach was used to obtain a sample size of 80 respondents from the population of seventh grade female pupils. A digital POCT device was utilized to quantify the incidence of anemia variables based on hemoglobin (Hb) levels, while a structured questionnaire instrument was employed to gather data for knowledge variables. The Chi-Square test was used to assess the bivariate data analysis. According to the univariate analysis, 62.5% of the participants (50 respondents) had a decent level of knowledge, and 73.8% of the participants (59 respondents) did not suffer from anemia (Hb > 12 g/dL). With a p-value of 0.000 (p < 0.05), the results of the bivariate test were generated. Anemia is more common among female students at MTs Al Ihsan Doglo who have a higher degree of expertise, according to this study. School districts should keep an eye on students' iron pill use and improve their nutrition education programs.